Effects of biochar on uptake, acquisition and translocation of silver nanoparticles in rice (Oryza sativa L.) in relation to growth, photosynthetic traits and nutrients displacement. (July 2019) - Abbas, Qumber; Liu, Guijian; Yousaf, Balal; Ali, Muhammad Ubaid; Ullah, Habib; Ahmed, Rafay
Abstract: Rapid development in nanotechnology and incorporation of silver nanoparticles (AgNPs) in wide range of consumer products causing the considerable release of these NPs in the environment, leading concerns for ecosystem safety and plant health. In this study, rice ( Oryza sativa ) was exposed to AgNPs (0, 100, 200, 500 and 1000 mg L −1 ) in biochar amended (2 %w/v) and un-amended systems. Exposure of plants to AgNPs alone reduced the root and shoot length, biomass production, chlorophyll contents, photosynthesis related physiological parameters as well as macro-and micronutrients in a dose dependent manner. However, in case of biochar amendment, physiological parameters i.e., net photosynthesis rate, maximum photosynthesis rate, CO2 assimilation, dark respiration and stomatal conductance reduced only 16, 6, 7, 3 and 8%, respectively under AgNPs exposure at 1000 mg L −1 dose. Meanwhile, biochar at all exposure level of AgNPs decreased the bioaccumulation of Ag in rice root and shoot tissues, thus alleviated the phyto-toxic effects of NPs on plant growth. Moreover, results showed that biochar reduced the bioavailability of AgNPs by surface complexation, suppressing dissolution and release of toxic Ag + ions in the growth medium. The presence of biochar at least decreased 2-fold tissue contents of Ag even at highest AgNPs (1000 mg L −1 ) concentration. These finding suggested that biochar derived from waste biomass resources can be used effectively to prevent the bioaccumulation and subsequent trophic level transfer of emerging Ag nano-pollutant in the environment. Graphical abstract: Image 1 Highlights: Biochar effects on growth, physiological traits and AgNPs uptake by rice were studied. Biochar addition alleviated the toxic effects of Ag on plant growth and development. Adsorption of NPs on biochar decreased the accumulation and transfer of AgNPs ∼2-folds. Physiological changes in rice to AgNPs exposure were not-significant under biochar amendment. Nutrient acquisition rates are also regulated by biochar in NPs contaminated medium. Abstract : Biochar addition alleviates the toxic effects of AgNPs on plant growth, physiological traits and nutrient acquisition by decreasing accumulation and transfer of AgNPs.